Big Data Analysis and Storage - Khalid Adam, Ismail Hammad; Fakhreldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain; Mazlina, Abdul Majid (IEOM Society, 2015)
While technologies to build and run big data projects have started to mature and proliferate over the last couple of years, exploiting all potentials of big data is still at a relatively early stage. In fact, Big data is term refer to huge data sets, have high Velocity , high Volume and high Variety and complex structure with the difficulties of management, analyzing, storing and processing. Due to characteristic of big data it becomes very difficult to Management, analysis, Storage, Transport and processing the data using the existing traditional techniques. This paper introduces Big Data Analysis and storage. First we presents the Big data technology alongside it’s the significance of big data in the modern world and venture existing which are successful and essential in changing the idea of science into huge science and society as well. Following that, we present How Fast Data is Increasing and The Importance of Big Data. In addition, we discuss Big Data Technologies include (Big Data Frameworks and Platforms and Databases for Big Data). Moreover, we discuss Data Storage and Big Data Management and Storage. Then, we present Big Data Analysis and Management include (Big Data with Data Mining, Big Data over Cloud Computing and Hadoop Distributed File System (HDFS) and MapReduce). Furthermore, we also discuss big data modeling and big data security issues. Finally Conclusion and Future work.